Islam and State: A Study on Al-Mawardi and An-Nabhani’s thought and its Compatibility in Indonesian Context - Fathor Rohman; M Hilali Basya; Sopa Sopa (Laboratorium Prodi Pendidikan Agama Islam UNJ, 2021)
Even though study concerning Islam and politics has been conducted by many researchers, few of them investigating about compatibility of Islamic political thoughts, which originated from the classical and medieval periods that have been influencing Islamic political movements and thoughts in Indonesia, with Indonesian context. Thoughts of Imam al-Mawardi (lived in the 12th Century) and Taqiyuddin al-Nabhani (lived in the 20th Century) are some of them that should be mentioned in this regard. Islamic political thoughts of al-Mawardi become the main reference for Sunni Muslims who are majority in Indonesia, while Islamic political thought of al-Nabhani become the main guidance of HTI (Hizbut Tahrir Indonesia) movement of which its members and followers are many in Indonesia. This article investigates about the political thoughts of al-Mawardi and al-Nabhani concerning the relationship between Islam and state as well as their compatibility with Indonesian context. This study uses the library research in which its primary resources are books written by al-Mawardi entitled Al-Ahkam al-Sulthaniyah and al-Nabhani entitled Ad-Daulah al-Islamiyah. By utilizing qualitative content analysis, data were collected and analyzed. This article argues that the Islamic political thought of al-Mawardi has been adopted by majority of Indonesian Sunni Muslims with some adjustments with Indonesian context, so that his thoughts become compatible with the concept of modern nation-state of Indonesia. On the other side, Islamic political thought of al-Nabhani which developed within a spirit of resistance to Western (European) colonialism has been adopted and campaigned by HTI without adjustment with Indonesian context. This causes al-Nabhani’s thought clashes with the concept of modern nation-state of Indonesia.